PENINGKATAN BELAJAR MATEMATIKA TENTANG PENGERJAAN HITUNG BILANGAN BULAT MELALUI BERBAGAI MEDIA - Anita Anita (Universitas Tanjungpura, 2018)
Abstract: To improve learning outcomes especially to accelerate the mastery of subject matter at elementary school level, the need for improvements in teaching and learning process through learning improvement program, especially in Mathematics subjects in order to obtain learning mastery. At Teluk Teluk State Elementary School, Kec, Nanga Pinoh Kab. Melawi found that students' learning outcomes were not appropriate for their absorption. Students were considered successful in classical learning when their absorption rate was 85% or more, and scored above 6.5. In accordance with the assessment technical guidance, if the student did not achieve the absorptive capacity 85 % and scores below 6.5, educators classify these students as students with low learning outcomes. In the learning process that is conveyed to 20 students of class V in daily examination, recorded students who master the subject matter with a value above 6.5 only 6 people (30%) and 14 0rang students (70%) have not been able to master the subject matter. During the learning process, the absence of students asking questions or responding to teacher explanations. Based on these findings, the authors asked colleagues to identify the shortcomings of the lessons learned.